Tờ trình tóm tắt về dự kiến Chương trình xây dựng luật, pháp lệnh năm 2022, điều chỉnh Chương trình xây dựng luật, pháp lệnh năm 2021 - UBTVQH (2021)
Toàn văn Tờ trình tóm tắt về dự kiến Chương trình xây dựng luật, pháp lệnh năm 2022, điều chỉnh Chương trình xây dựng luật, pháp lệnh năm 2021